(Semantic Openness in Sūrat al-Mulk: A Linguistic and Rhetorical Study) (Journal of the College of Basic Education, 2026)
This study, entitled (Semantic Openness in Sūrat al-Mulk: A Linguistic and Rhetorical Study) focuses on semantic openness in Sūrat al-Mulk from linguistic and rhetorical perspectives, examining the nature of open meaning and its capacity for renewal in accordance with context and linguistic structure. The study consists of an introduction and two main sections. The introduction addresses the concept of semantic openness from both linguistic and rhetorical viewpoints, as well as semantic openness in Qur’anic discourse. The first section discusses the semantic openness of expressions of address and guidance, the Beautiful Names of Allah, and major key terms, clarifying how words move from a literal meaning to broader cognitive, emotive, and contemplative horizons through declarative statements, interrogative forms, and implicit imperatives, thereby enabling the addressee to participate in the production of meaning. The second section examines the semantic openness of binary oppositions such as antithesis and parallel contrast, as well as figurative imagery such as metaphor and simile, highlighting their role in expanding meaning and enriching intellectual and emotional engagement. Finally, the study concludes by presenting its main findings, along with a list of sources and references.